Endoscope-assisted Transorbital Keyhole Surgical Approach to Ruptured Supratentorial Aneurysms - Ho, Chi Long; Hwang, Peter Y. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Background Many different surgical approaches have been described to treat intracranial aneurysms. A common feature of all the approaches has been relatively extensive brain exposure and brain retraction with increasing surgical morbidity. Transorbital keyhole is one of the minimally invasive approaches. Endoscope-assisted transorbital keyhole surgery (EATOKS) combines minimally invasive transorbital keyhole surgery with endoscope-assisted microneurosurgery. We describe our experience with this approach and its efficacy in treating ruptured supratentorial aneurysms.Materials and Method We retrospectively reviewed 62 patients (18 men [29%] and 44 women [71%]) with a ruptured supratentorial aneurysm who underwent surgical clipping via the EATOKS approach from April 2003 to July 2012. In all our cases, we use a rigid endoscope of 0, 30, or 45 degrees to inspect the aneurysm and its surrounding anatomy before clipping and ultimately to verify the completeness of the aneurysm clipping and the patency of the adjacent neurovascular structures.Results All patients with ruptured supratentorial aneurysms were successfully clipped including three with multiple aneurysms. Surgically related major and minor as well as medically related complications were 10%, 15%, and 10%, respectively. Three patients (4.8%) died of massive cerebral infarction due to fulminant postoperative vasospasm, multiorgan failure, and adult respiratory distress syndrome. At 6-month follow-up, 81% of patients achieved good outcomes with Glasgow Outcome Scales of 4 and 5. Patients' satisfaction with the cosmetic results was satisfactory to excellent in most cases.Conclusion EATOKS is a viable and safe option in the neurosurgical armamentarium to treat ruptured supratentorial aneurysms.
Keywords: aneurysms; endoscope assisted; minimally invasive; transorbital keyhole